O co chodzi w paradoksie Protagorasa? - Łukowski, Piotr (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2005)
The ancient paradox of Protagoras had the opinion of an unsolved problem. The two solutions proposed in the 20th century by W. Lenzen and L. Aqvist are considered to be the best. In fact none of them may be treated as proper. In the paper we show that both of authors avoid contradiction solely by means of mere neglect. However quite a simple solution seems to be feasible when the paradox is approached as an amphibolic construction, thus an ambiguity.